Development of novel methods for the detection of Vibrio parahaemolyticus in seafood - Pai, Namrata (2003)
Vibrio parahaemolyticus is marine bacterium found worldwide. It is most commonly associated with seafood related gastroenteritis, but can also be found naturally occurring in the estuarine environment. Infection is most common in the summer months, when the water temperature is suitable for the growth of bacteria. The infection is usually self limiting but morbidity can result in some cases. Currently very few methods are in use for rapid detection of this organism. In addition, these methods are not always specific and can give false positive reactions. This study describes the development of a novel method, based on phage antibody display, for the detection of V. parahaemolyticus in seafood. The initial part of the study focuses on the use of the Polymerase Chain Reaction (PCR) as a rapid method for the detection of V. parahaemolyticus. Four sets of primers were used for PCR, of which three were targeted to the toxin producing genes. The sensitivity and specificity of these primers in PCR was tested using pure cultures of V. parahaemolyticus and non parahaemolyticus spp. Homogenised oyster tissue was then seeded with these cultures and they were tested again by PCR. A semi-synthetic scFv bacteriophage antibody library was used to isolate bacteriophage antibodies against V. parahaemolyticus. After five rounds of panning, the clones were further tested by ELISA and flow cytometry. At least four of the clones showed a strong binding profile with strains of V. parahaemolyticus. These clones also did not cross-react with other Vibrio spp. Similar to the PCR reaction, the clones were tested by seeding oyster homogenate with bacterial cultures. It was found that the ELISA reaction was inhibited by the presence of oyster homogenate. Therefore, a3h pre-enrichment step was necessary before testing for the presence of bacterial cells. The phage antibody clones which showed strong binding in pure culture still retained their binding capacity, when tested in the presence of seafood (oyster homogenate). The sensitivity of the assay was further increased by using chemiluminescence detection of phage binding. The data also suggests that this method has the potential sensitivity to detect V. parahaemolyticus at or below the current action level.
HydraID: hull:5591 Hydra Discover Access Group: public EThOS identifer: 412484 ETD Collection: ETDBiosciences
Keywords: Biological sciences